Surgical management of distal tibia fracture: towards an outcome-based treatment algorithm - Isnin, Rushdi; Che Ahmad, Aminudin; Abdul Ghani, Kamarul Haq; Mohd Rus, Razman (Malaysian Orthopaedic Association (MOA) and ASEAN Orthopaedic Association (AOA), 2020)
Introduction: Distal tibia fractures are frequently associated with an extensive soft tissue injury which then leads to a higher risk of complications such as infection, non-union and eventually poor overall outcome. The purpose of this study is to measure the outcome of distal tibia fractures treated with internal fixation, external fixator or Ilizarov external fixator(IEF). We aim to propose an algorithm for management of distal tibia fractures by evaluating the treatment options, outcomes and risk factors present. Material and Methods: This study is a cross-sectional study of all distal tibia fractures treated surgically in Tengku Ampuan Rahimah Hospital, Klang from 1st January 2016 till 30th June 2018. Patient records were reviewed to analyse the outcomes of surgical treatment and risk factors associated with it. distal tibia fracture, tibia pilon fracture, tibial plafond fracture, Ilizarov external fixator, internal fixation Results: Ninety-one patients were included with a mean age of 41.5 years (SD = 16.4). Thirty-nine cases (42.9%) were open fractures. Thirty-eight patients (41.8%) were treated with internal fixation, 27 patients (29.7%) were treated with IEF and 26 patients (28.6%) were treated with an external fixator. Among open fractures cases, no significant finding can be concluded when comparing each surgical option and its outcome, although one option was seen better than the other in a particular outcome. Initial skeletal traction or temporary spanning external fixator in close fractures reduced the risk of mal-alignment (p value=0.001). Internal fixation is seen superior to IEF and external fixator in close fractures in term of articular surface reduction (p value = 0.043) and risk of mal-alignment (p value = 0.007). Conclusion: There is no single method of fixation that is ideal for all pilon fractures and suitable for all patients. This proposed algorithm can help surgeons in deciding treatment strategies in the challenging management of distal tibia fractures to reduce associated complications.